Review of New Zealand Coastal Marine Invertebrates 1―an illustrated compendium edited by S. Cook (2010) - Gordon, Dennis P. (Zootaxa, 2010)
This outstanding work is the culmination of a publishing project that began twenty years ago. Originally planned as a three-year project and initiated in November 1990, the goal was to produce a single-volume identification guide, illustrating a majority of the coastal macroinvertebrate species of New Zealand. These would be species larger than one centimetre in size, found on the seashore and encountered within the depth range visited by the average scuba diver. In the event, as tends to happen with visionary projects, the time frame grew, largely owing to human factors, and a second volume will be published in 2012 to complete the series. Though a long time coming, this first volume was worth the wait―it is truly a milestone in New Zealand natural-history publishing. Canterbury University Press is to be congratulated in taking it on and the editor, who initiated and coordinated the project, in seeing it through to the end.